2021
DOI: 10.15678/znuek.2020.0989.0502
|View full text |Cite
|
Sign up to set email alerts
|

Female Careers in Italian Universities: The Role of Gender Budgeting to Achieve Equality between Women and Men

Abstract: Calabrese wrote the paragraph "Results & Discussion", M. C. Fede wrote the paragraph "The Role of The Central Guarantee Committee for Equal Opportunities in Universities", V. Naciti wrote the paragraphs "Introduction" and "Theoretical Background", while N. Rappazzo wrote the paragraphs "Gender Budgeting and Gender Auditing in Public Administrations" and "Conclusion". This is an open access article distributed under the terms of the Creative Commons Attribution--NonCommercial-NoDerivatives 4.0 License (CC BY-NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Women carry much more family responsibility than their male colleagues. This has been reflected in a late return to physical workplaces with respect to men (Calabrese et al, 2021). A recent study that investigated the role of women during the COVID‐19 crisis, revealed that women are seen as more effective leaders with respect to their men colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…Women carry much more family responsibility than their male colleagues. This has been reflected in a late return to physical workplaces with respect to men (Calabrese et al, 2021). A recent study that investigated the role of women during the COVID‐19 crisis, revealed that women are seen as more effective leaders with respect to their men colleagues.…”
Section: Introductionmentioning
confidence: 99%